Influence of running shoe longitudinal bending stiffness on running economy and performance in trained and national level runners - Rodrigo-Carranza, V.; Hoogkamer, W.; Salinero, J. J.; Rodríguez-Barbero, S.; González-Ravé, J. M.; González-Mohíno, F. (Medicine & Science in Sports & Exercise, 2023)
Introduction/purpose Previous results about shoe longitudinal bending stiffness (LBS) and running economy (RE) show high variability. This study aimed to assess the effects of shoes with increased LBS on RE and performance in trained and national runners.